Reconstruction of a ruptured patellar tendon using ipsilateral semitendinosus and gracilis tendons with preserved distal insertions: two case reports - Takazawa, Yuji (BioMed Central, 2013)
BACKGROUND: Acute patellar tendon ruptures with poor tissue quality. Ruptures that have been neglected are difficult to repair. Several surgical techniques for the repair of the patellar tendon have been reported, however, these techniques remain difficult because of contractures, adhesions, and atrophy of the quadriceps muscle after surgery. CASE PRESENTATION: We report the cases of 2 Japanese patients (Case 1: a 16-year-old male and Case 2: a 43-year-old male) with patellar tendon ruptures who were treated by reconstruction using semitendinosus-gracilis (STG) tendons with preserved distal insertions. Retaining the original insertion of the STG appears to preserve its viability and provide the revascularization necessary to accelerate healing. Both tendons were placed in front of the patella, in a figure-of-eight fashion, providing stability to the patella. CONCLUSION: Both patients recovered near normal strength and stability of the patellar tendon as well as restoration of function after the operation.